909 Understanding patient and parental experience in paediatric research – reflections from the Translational Research in Intestinal Physiology and Pathology (TRIPP) study. (17th August 2022) - Natasha, G; Glemas, Claire; Zilbauer, Matthias
Abstract : Aims: Patient and public involvement is essential to improve the quality of research, gain unique insights from the patient's perspective, and improve subject recruitment. This is particularly pertinent in the paediatric setting, where there are unique ethical, legal and technical challenges. Nonetheless, research in paediatrics is of paramount importance in order to understand disease, and ultimately drive improvements in patient care and health outcomes. The Translational Research in Intestinal Physiology and Pathology (TRIPP) study investigates the role of epigenetics in the intestinal mucosa, and recruits paediatric patients from all age groups. We aimed to determine the study recruitment rate of paediatric patients and their families who were invited to participate in the TRIPP study, explore factors that influence their decision making, understand their perceptions surrounding paediatric research and highlight any areas for improvement. Methods: A cross-sectional survey was undertaken between 11 th January 2022 and 2 nd February 2022 at a single tertiary centre where the TRIPP study is actively recruiting. Families that were invited to participate in the TRIPP study were provided a self-administered questionnaire to complete. This included both qualitative and quantitative metrics to explore their perceptions and experience from participating in paediatric research. Both paper-based and electronic questionnaires were made available at time of consenting. Results: A total of 22 patients or their families completed the questionnaire, of which, 100% consented (22/22) to be part of the TRIPP study. 14% (3/22) of patients are above 15 years, 59% (13/22) are between 10 - 15 years, 23% (5/22) are between 1 - 4 years, and 4% (1/22) are < 1 year old. 77% (17/22) of patients consented with their parent, and 23% (5/22) of parents consented on behalf of their child. The top three reasons that were important for taking part in paediatric research were clinical benefit, safety and study practicalities, as cited by 82% (18/22), 68% (15/22) and 59% (13/22) respectively. 73% (16/22) strongly agreed and 18% (4/22) agreed that they will participate in research again. 1 patient remained neutral and 1 did not answer. Qualitative feedback was similarly very positive. One reported that they have 'done research before and think it is good'. Another patient felt 'you do a great job, but there can never be too much communication. I think that a deeper understanding of the purpose of a study is really beneficial to those involved. Also, involve the young person - clear, engaging information aimed at them?'. Other areas for improvement include that 'using the acronym TRIPP is not necessarily meaningful to the patient and patient families as they may agree to research but not remember what it is called'. Conclusion: Overall, our preliminary results suggest there is a high study recruitment rate amongst the patients approached for the survey. Moreover, it is encouraging that most respondents report they are willing to participate in paediatric research in future. One limitation is that we did not survey patients who did not consent to the study, and ongoing work aims gain feedback from a larger cohort to explore this further.